Establishment of a cho cell line by over-expression of the X-linked inhibitor of apoptosis - Liew, Jane Chiar Jenn (2012)
In mammalian cell culture, serum deprivation inhibits cell growth and induces apoptosis. Adapting host cells to serum-free medium is difficult and time-consuming,therefore anti-apoptosis engineering of mammalian cells were used to account the problems caused by serum deprivation. The X-linked inhibitor of apoptosis protein (XIAP) is the most effective member of the inhibitor of apoptosis protein (IAP) family, where it inhibits apoptosis by retarding the downstream caspase activity in the apoptosis chain cascade. In an attempt to investigate the ability of XIAP to delay serum-deprived-induced-apoptosis, stable CHO-K1 cell lines expressing the XIAP proteins were established by introducing the XIAP gene into the host genome. Transfected cells with high expression of XIAP were selected by conducting the MTT assay and flow cytometric analysis. Selected cell line was cultured and closely examined under several serum-deprived conditions. During exposure to serum deprived medium, cells expressing XIAP showed decreased level of apoptosis and a higher number of viable cells compared to the control cell lines. The viability of control cells dropped to 40% after 2 days of serum deprivation, while the XIAP expressing cells still maintained at a viability over 90%, where caspase-3 activity was found to be inhibited. Meanwhile, the study also showed that CHO-K1-XIAP cells exhibited a slower growth profile, where most of the cells were found to be located in the G0/G1 phase. The results suggest that the over-expression of XIAP induces G0/G1 growth arrest, where proliferation was retracted, leading to a 50% reduction in maximum cell density. In the following attempt to investigate the productivity of the established cell line,the CHO-K1-XIAP cell line was then co-transfected with cycle-3 green fluorescent protein (GFP), as a model protein to access the productivity of the cells. Cells were cultured under serum-deprived condition with addition of sodium butyrate (NaBu) treatment in various concentrations. NaBu is widely used to boost up the commercial production of recombinant proteins, but was found to be cytotoxic and causes rapid apoptotic cell death in mammalian cell cultures. Upon subjecting the cells to serumdeprived and NaBu-induced condition, the control significantly declines in cell viability and GFP production. The CHO-K1-GFP expressing XIAP remained robust and continued to express GFP for the initial 2 days, having a 52% increment of high GFP producers. Moreover, the results indicated that the intracellular levels of GFP were further increased while cells became progressively growth-arrested, shifting 33% of the low GFP producers to high GFP producers. Although XIAP over expression could not effectively inhibit NaBu-induced apoptosis, however, a 35% reduction of caspase-3 activation was observed in CHO-K1-XIAP-GFP cells at its termination point. Taken together, host cells solely expressing a single type of anti-apoptotic protein are found to be inadequate in regard to extension of culture longevity and enhancement of protein production. Therefore, for a better and more effective apoptosis inhibition, a combination of caspases inhibitor and mitochondrial dysfunction should be considered in future studies.